Highly Ordered N‐Doped Carbon Dots Photosensitizer on Metal–Organic Framework‐Decorated ZnO Nanotubes for Improved Photoelectrochemical Water Splitting - Sudhagar Pitchaimuthu (Small, 2019)
In spite of having several advantages such as low cost, high chemical stability, and environmentally safe and benign synthetic as well as operational procedures, the full potential of carbon dots (CDs) is yet to be explored as photosensitizers due to the challenges associated with the fabrication of well‐arrayed CDs with many other photocatalytic heterostructures. In the present study, a unique combination of metal–organic framework (MOF)‐decorated zinc oxide (ZnO) 1D nanostructures as host and CDs as guest species are explored on account of their potential application in photoelectrochemical (PEC) water splitting performance. The synthetic strategy to incorporate well‐defined nitrogen‐doped carbon dots (N‐CDs) arrays onto a zeolitic imidazolate framework‐8 (ZIF‐8) anchored on ZnO 1D nanostructures allows a facile unification of different components which subsequently plays a decisive role in improving the material's PEC water splitting performance. Simple extension of such strategies is expected to offer significant advantages for the preparation of CD‐based heterostructures for photo(electro)catalytics and other related applications.